1999
DOI: 10.1063/1.124934
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of asymmetric giant magnetoimpedance in field-annealed Co-based amorphous ribbon

Abstract: The asymmetric giant magnetoimpedance (GMI) profile has been realized in weak-field-annealed Co-based amorphous ribbon at the annealing temperature of 380 °C in open air. Asymmetric GMI profiles with respect to applied field become profound as the annealing field increases over 500 mOe. The asymmetric GMI profile at the frequencies of ac current over 0.5 MHz is well ascribed for by the rotational transverse magnetization of single domain under a uniaxial anisotropy in amorphous core and a unidirectional anisot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 10 publications
2
27
0
2
Order By: Relevance
“…A typical result shown in the literature is to have an ultra-high fracture strength of 5185 MPa for a Co 43 Fe 20 Ta 5.5 B 31.5 amorphous alloy [4]. Furthermore, particular examples of interest are to use them for the soft magnet-tube and micro-electronic core applications [5,6]. Besides, it may be also important to understand their thermal-activated degradation in oxidizing atmospheres when using those alloys at elevated temperatures in ambient environments.…”
Section: Introductionmentioning
confidence: 97%
“…A typical result shown in the literature is to have an ultra-high fracture strength of 5185 MPa for a Co 43 Fe 20 Ta 5.5 B 31.5 amorphous alloy [4]. Furthermore, particular examples of interest are to use them for the soft magnet-tube and micro-electronic core applications [5,6]. Besides, it may be also important to understand their thermal-activated degradation in oxidizing atmospheres when using those alloys at elevated temperatures in ambient environments.…”
Section: Introductionmentioning
confidence: 97%
“…I600 alloy is normally nonmagnetic, but it has little magnetic response under the operating condition of steam generator [2]. Recently developed Co-based amorphous giant magnetoimpedance (GMI) sensor shows the high field sensitivity over 1000%/Oe [3]. In this study, the change of GMI signals were measured in the thermal aged I600 alloy as a function of ageing time at various temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…We reported that the asymmetric GMI effect in the field-annealed ribbon due to the bias field produced by hard magnetic layer formed near the surface during annealing [5,12].…”
Section: Introductionmentioning
confidence: 99%